2017
DOI: 10.5433/1679-0359.2017v38n2p635
|View full text |Cite
|
Sign up to set email alerts
|

Graft incompatibility in Prunus spp. preceded by SPAD index reduction

Abstract: This study aimed to measure the leaf chlorophyll index (SPAD 502 Plus) in three peach cultivars grafted on different clonal rootstocks, totaling 68 scion/rootstock combinations, between five and nine months after planting in the field to determine possible graft incompatibility symptoms in Prunus spp. Three field trials with peach scion cultivars 'BRS-Kampai', 'Jade', and 'Maciel' grafted on 18, 25, and 25 clonal rootstocks, respectively, were established in July and August 2014. Own-rooted scion trees (withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
2
7
0
1
Order By: Relevance
“…However, the overall yield average observed in the present study resembles that found in southern Brazil (Barreto et al, 2017), northern Tunisia (Yahmed et al, 2016) and northern and southern Italy (Scalisi et al, 2018). (Zarrouk et al, 2006;Neves et al, 2017) and in pear (Melo et al, 2017), in order to introduce useful characteristics such as vigor control, pest resistance and edaphoclimatic adaptation, such a combination does not always result in success.…”
Section: Heritability Of Individual Plots Average Genotype Heritabilsupporting
confidence: 59%
“…However, the overall yield average observed in the present study resembles that found in southern Brazil (Barreto et al, 2017), northern Tunisia (Yahmed et al, 2016) and northern and southern Italy (Scalisi et al, 2018). (Zarrouk et al, 2006;Neves et al, 2017) and in pear (Melo et al, 2017), in order to introduce useful characteristics such as vigor control, pest resistance and edaphoclimatic adaptation, such a combination does not always result in success.…”
Section: Heritability Of Individual Plots Average Genotype Heritabilsupporting
confidence: 59%
“…values did not decrease in other scion/rootstock combinations after 9 months of planting, indicative of their compatibility (Figures 5A,B; Neves et al, 2017). Thus, SPAD chlorophyll meter serves as an effective and non-destructive tool for the prediction of incompatible graft combinations.…”
Section: Graft Incompatibility: Types and Determining Techniquesmentioning
confidence: 74%
“…The rootstocks showing translocated graft incompatibility symptoms like reddening of leaves, excessive leaf curling, leaf drop, etc., with scion cultivars died 5 months after planting. SPAD index values did not decrease in other scion/rootstock combinations after 9 months of planting, indicative of their compatibility ( Figures 5A,B ; Neves et al, 2017 ). Thus, SPAD chlorophyll meter serves as an effective and non-destructive tool for the prediction of incompatible graft combinations.…”
Section: Graft Incompatibility: Types and Determining Techniquesmentioning
confidence: 87%
“…A incompatibilidade de enxertia de 'Mirabolano 29C' com 'BRS Libra' já foi observada por Pressi (2015) na região sul do Brasil, em Chapecó-SC, onde o portaenxerto apresentou engrossamento excessivo do caule e induziu baixo vigor à cultivar copa. Neves et al (2017) também verificaram que tanto 'Marianna 2624' quanto 'Mirabolano 29C' reduziram os índices de clorofila em folhas e ocasionaram morte de plantas das cultivares Kampai, Jade e Maciel.…”
Section: Resultsunclassified